ANALISIS TAX PLANNING ATAS PAJAK PENGHASILAN BADAN PADA PT MADU BARU - , PAULA SOFYANITA, Ahmad Amin, S.E., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this research was to identify accounts involved in income tax planning applied in 2011 by PT Madu Baru. Afterwards, the result of identification was analysed to know the tax planning strategy did by the company. Based on the research result, known that in 2011 PT Madu Baru had been applied tax planning. The strategy was maximizing fiscal cost, delay obligation pay, avoid infraction related to tax rules, and choosing depreciation method. In applying the strategy, there are some evaluation could be done to optimize the former strategy resulting the company get a benefit as a tax saving Rp 371.102.872,66.